An Electronic Health Record Intervention for Advance Care Planning in an Emergency Department - Hall, Holley (My University, 2021)
Advance directives help preserve patient autonomy and decision-making in situations where they cannot use their voice. Unfortunately, many individuals do not have an advance directive (AD), raising the concern for a poor patient experience, increased healthcare costs, and moral distress in family members and healthcare providers. The purpose of this quality improvement project was to design an AD screening tool to be utilized in an emergency department electronic health record (EHR) to improve screening and documentation of ADs and enhance patient awareness through education via the patient portal. Over 12-weeks, there was an improvement in screening tool utilization from 47% to an average of 56.6%, submission of 12 AD documents to the EHR, and 45 patients who requested education to be sent to their patient portal. Throughout implementation, the emergency department had 9,810 patient encounters, and 317 (3.2%) patients reported having an advance directive. Unfortunately, that leaves more than 90% of the patients without having an advance directive emphasizing the need to continue to improve patient awareness of the importance of advance care planning.
Keywords: advance directive; advance care planning; electronic health record; portal-based education; patient electronic messaging; patient autonomy; emergency department